RESEARCH TITLE: "STUDY OF FACTORS INFLUENCING MORBIDITY AND ROLE OF DEXAMETHASONE IN LABORATORY-CONFIRMED DENGUE PATIENTS: A SINGLE CENTRE RETROSPECTIVE ANALYSIS" - Dr. Abhishek Karmalkar; Deepak Bagde (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Dengue is a significant global health concern, particularly in tropical and subtropical regions. Understanding the factors influencing morbidity and the potential benefits of treatments like Dexamethasone is crucial for improving patient outcomes. This study focuses on the clinical and laboratory parameters that predict ICU admission and evaluates the role of Dexamethasone in managing severe Dengue cases.Objectives: The study aims to determine the incidence of Dengue patients requiring critical care and extended hospital stays, identify clinical and laboratory risk factors associated with ICU admission, and investigate the effect of steroids, specifically Dexamethasone, in reducing hospital stay and complications in laboratory-confirmed Dengue patients.Methodology: This observational, retrospective study used medical records of laboratory-confirmed Dengue patients at Vedant Hospital, Pimpri, Pune. Data collected included demographic information, clinical presentation, laboratory parameters, severity indicators, steroid usage, total length of stay, and ICU duration.Results: Among 200 patients, 58% were male and 42% female, with a majority (94%) residing in urban areas. ICU admissions showed no significant associations with gender, address, or age. Decreased appetite (69% ICU vs. 39.4% non-ICU, p